Cerebral Cortical and White Matter Lesions in Amyotrophic Lateral Sclerosis with Dementia: Correlation with MR and Pathologic Examinations - Matsusue, E.; Sugihara, S.; Fujii, S.; Kinoshita, T.; Nakano, T.; Ohama, E.; Ogawa, T. (American Journal of Neuroradiology, 2007)
BACKGROUND AND PURPOSE: Amyotrophic lateral sclerosis with dementia (ALSD) is a progressive neurodegenerative disorder, characterized clinically by motor neuron symptoms and dementia, and pathologically by degeneration of the motor neurons of the brain and spinal cord as well as atrophy of the frontal and/or temporal lobes. So far, there has been no study on the correlation of MR images with histologic findings in ALSD. We studied the correlation of antemortem and postmortem T2-weighted MR images with histologic findings in autopsy-proved cases of ALSD.MATERIALS AND METHODS: Antemortem and postmortem T2-weighted images were compared with histologic findings in 3 autopsy-proved cases of ALSD.RESULTS: Antemortem MR images showed atrophy of the frontal and temporal lobes, which were asymmetric in the medial-ventral part of the temporal lobe. Faint linear T2-hyperintensity was seen in the medial-ventral part of the temporal subcortical white matter in 1 case. Postmortem T2-weighted images showed linear subcortical hyperintensity in the ventral-medial temporal lobe in each case. Histologically, cortical atrophy on MR images showed spongiform change with neuronal loss and gliosis especially in the superficial layers and linear subcortical hyperintensity on T2-weighted images showed degeneration and gliosis in each case. These findings are characteristic histologic changes of ALSD.CONCLUSION: MR imaging of atrophy of the frontal and temporal lobes with linear subcortical hyperintensities in the anteromedial temporal lobe is useful for diagnosis of ALSD.